Customer Relationship Management In The Digital Era To Enhance Customer Experience Through Technology - Naim, Ifin; Rajuddin, Wa Ode Nursaadha; Ansyori, Ahmad (Transforma Jurnal Manajemen, 2024)
In the digital era, customer relationship management (CRM) has undergone a significant transformation with the advent of advanced technology that facilitates more effective interactions between companies and customers. Digital CRM allows companies to collect, analyze and utilize customer data in real-time, thereby offering a more personalized and relevant experience. Technologies such as artificial intelligence, big data and predictive analytics have played an important role in optimizing CRM strategies. Through the use of chatbots, automated personalization, and data analysis, companies can increase customer satisfaction and brand loyalty. Implementing digital CRM not only helps in understanding customer needs and preferences, but also enables companies to respond quickly and appropriately to changes in customer behavior. This study explores how digital technology has changed traditional CRM approaches and provided competitive advantages for companies. In addition, this research also highlights the challenges faced in implementing digital CRM, including issues of data privacy and information security. In conclusion, technology integration in CRM is the key to improving customer experience in the digital era, making interactions with customers more effective and efficient. Thus, companies that successfully adopt digital CRM can create stronger and more sustainable relationships with their customers.